EFEKTIFITAS PIJAT OKSITOSIN OLEH SUAMI TERHADAP PRODUKSI ASI - Selma " Salsabilla; Misrawati " "; Wasisto " Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Breastfeed is the healthy fluid produced by a mother. Oxytocin massage had use to an alternative therapy for increasing breastfeed’s volume. Oxytocin massage is a helpfull way to help mother’s body produces the breast feeding which the partner should give their hand on this process. Partner support and involvement help to stimulate mom’s body to produce and increasing breastfeed’s volume. The aim of this study was to determine the effectiveness of oxytocin massage by partner on breastfeed’s volume. This study has conducted in the community health center Sidomulyo Pekanbaru by having quasy experiment and pre test-post test design with control group approach. This method took purposive sampling for 38 respondents. Nineteen respondents for experimental group and another is for the control group. Intervention gave along 3 days attending to 10 minutes oxytocin massage by partner each day. Measuring equipment in this study used the breastfeed bottle to muasure breastfeed’s volume. The result is analyzed by univariat analysis that describes the distribution of frequences and bivariat analyze by using Mann-Whitney and Wilcoxon. The result showed that p value post test for experimental group 0,000 to controlling group. This result showed us that the massage by their partner gives a positive effect for breastfeed’s volume. The massage of this study is expected to be one of the nursing interventions to increase the volume of breastfeed. Key word               : Breastfeed, Oxytocin Massage, Partner